(untitled) (Research, Society and Development, 2022)
The SARS-CoV-2, popularly know as Coronavirus, was identified in Wuhan, China, in December 2019. The accelerated contagious dissemination of COVID-19 lead the World Health Organization to declare Public Health Emergency of International Concern (PHEIC) in 2020. In order to contain the fast dissemination, social distancing measures were adopted, which caused challenges in different contexts. In the educational field, the Minister of Education decreed the substitution of in person classes for the emergency remote teaching. The ADHD is a neurobiological disorder characterized by a persistent pattern of inattention and/or hyperactivity-impulsivity, which interferes in the functioning, development and teaching-learning process of individuals in this condition. Previous studies pointed out the implications that new digital technologies can have in the learning/development of schoolers with ADHD. Likewise, it was highlighted that the didactic methodology used by teachers should favor the development and behavior of children with ADHD. In this context, a bibliographic review was made to describe the results of research that evaluate the perception of remote teaching in children diagnosed with ADHD, their parents and teachers, in order to know the easiness and difficulties in the use of virtual learning environments. Inconsistent results were observed about the impact of remote teaching on children and teenagers with ADHD, for some studies pointed its benefits while others pointed its harms. It is concluded that future research is needed to clarify the disparities and the factors that interfere in the results and facilitate or hinder the process of teaching-learning in students with ADHD.